Composition and Density of Fouling Organism on the Wood Harbour at Karang-Karangan, Bua District, Luwu Regency - Elki Julianto P; Magdalena Litaay; Dody Priosambodo (Universitas Hasanuddin, 2018)
The Research on Composition and Abundance of Biofouling Biota at Woodenpier at Karang-Karangan Beach Bua Sub-district of Luwu Regency was conducted from December 2016-June 2017. The purpose of this research is to know the types of macrobiofouling, and the abundance of macrobiofouling on the wooden pier on the Beach Coral-Karangan, Bua Sub-district, Luwu Regency. Sampling method using a quadrant plot and performed two data retrieves on the poles of wooden pier which were either exposed or unexpressed by water with 12 point stations. The results showed there were 8 species of 6 families: Saccostrea sp (ostreidae), Saccostrea cucullata (Ostreidae), Littoraria scabra (Littorinidae), Thais rufotincta (Muricidae), Septifer sp (Mytilidea), Cladophora glomerata (Cladophoraceae), Balanus sp (Balanidae), and Haemocinus sp (Planopilumnidae). Saccostrea sp has the highest average abundance ofmacrobiofouling on exposed wooden pier (223 ind/m 2). The lowest abundance of Thais rufotincta and Haemocinus sp (1 ind/m2), respectively.